2018
DOI: 10.21037/atm.2018.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery for thoracolumbar spinal trauma

Abstract: The indications for operative intervention after thoracolumbar spine trauma have been well described. Advances in minimally invasive techniques, including percutaneous pedicle screw fixation and mini-open anterolateral retractor-based approaches can improve surgical outcomes when appropriately applied by reducing blood loss, operative duration and post-operative pain. Moreover, they allow for theoretical advantages by preservation of muscular and skeletal blood supply and innervation that is typically lost dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 43 publications
0
37
0
3
Order By: Relevance
“…MI techniques have shown benefits over open corpectomies, both in our data here and in prior studies. 11,[14][15][16]26 Thus, we believe the addition of anterior column reconstruction in the management of burst fracture, using an MI technique, has clear benefit to the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MI techniques have shown benefits over open corpectomies, both in our data here and in prior studies. 11,[14][15][16]26 Thus, we believe the addition of anterior column reconstruction in the management of burst fracture, using an MI technique, has clear benefit to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 To our knowledge, few studies have examined the role of the MI lateral approach accompanied by anterior column reconstruction (MI lateral corpectomy) in a trauma population. [14][15][16] The indications for surgery in thoracolumbar trauma have evolved with improvements in diagnostic testing. The thoracolumbar injury classification and severity (TLICS) system characterizes fracture morphology, posterior ligamentous complex (PLC) integrity, and neurological status.…”
mentioning
confidence: 99%
“…In addition, patients who underwent conservative treatment experience poor quality of life and high nursing costs. The pedicle screw system, especially the minimally invasive internal fixation surgery, enables faster recovery of the after internal fixation and patients can immediately resume their normal activities of daily living [ 5 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of three-dimensional computed topography (CT) navigation during surgery can effectively reduce the rate of injury to articular process joints, it has not yet been widely promoted in Chinese hospitals because of its high cost and the high-end technology required for navigation, and most hospitals still use two-dimensional C-arm X-ray machines for the positioning of percutaneous pedicle screws under uoroscopy. Anatomical imaging studies of vertebral pedicles have demonstrated that from L1 to L5, the transverse inclination angle of the pedicle gradually increases, and the transverse diameter of the pedicle isthmus gradually widens [2][3][4] . The distance between the projection of the pedicle axis on the back of the corpus vertebrae and the ipsilateral articular process joint gradually increases.…”
Section: Introductionmentioning
confidence: 99%